Economic Impact on Oral Health Care Practices of Rural People of Lalitpur District, Nepal - Sakha, Amit Kumar; Silwal, Uma Kant (Nepal Journal of Multidisciplinary Research, 2019)
People should be conscious for the proper caring of health and immediate response on health problem because creative mind is the output of sound health. Oral health problem is also sensitive issue so it should be cared properly with timely treatment. The main objective of this study is to identify the economic impact on oral health practices of rural people of Lalitpur district of Nepal. The study was conducted among the 369 oral health patients and discussed about their economic status and its impact on their health seeking practices. The result found that there was no significant impact of economic status on their oral health practices. Socio-cultural and other environmental factors may be responsible to determines the oral health practices so future researchers can study on the role of other socio-cultural factors on oral health practices.